Analisis Kestabilan Lereng Pada Overburden Lempung menggunakan Metode Fellenius : (Studi Kasus Blok Parasi PT. Wijaya Inti Nusantara Kabupaten Konawe Selatan) - Ashar, Ashar; Usman, Ida; Siharis, Al Amin; Abriansyah, Abriansyah; Amin, Fitrani; Shaddad, Aqsal Ramadhan; Aldiyansyah, Aldiyansyah (Universitas Muhammadiyah Kendari, 2025)
This study analyzes slope stability using the Fellenius Method in the Parasi Block of PT Wijaya Inti Nusantara, South Konawe Regency. The objective is to determine the safety factor (SF) as well as the safe and efficient slope geometry. Data were obtained from field measurements and laboratory tests of unit weight, cohesion, and internal friction angle. Calculations were performed manually and using Slide 6.0 software. The results indicate that the SF values for both single and overall slopes exceed 1.2, indicating stability in accordance with the Ministry of Energy and Mineral Resources Decree No. 1827 K/30/MEM/2018. However, the SF values decrease when influenced by groundwater levels. These findings can serve as a reference for planning safe and efficient slope designs in the mining area of PT Wijaya Inti Nusantara.